Perioperative Two-Dimensional Transesophageal Echocardiography A Practical Handbook - Vegas, Annette (Springer International Publishing, 2018)
Transesophageal echocardiography (TEE) is a valuable diagnostic modality now routinely used during cardiac surgery and in the intensive care unit. Increasingly, anesthesiologists, cardiologists and critical care physicians trained in TEE provide the service in both settings where they face the challenge of integrating numerous current TEE guidelines into day-to-day practice. Perioperative Two-Dimensional Transesophageal Echocardiography: A Practical Handbook, 2nd Edition has been designed to be a concise, portable guide for using TEE to recognize cardiac pathology during the perioperative period. This compact guide has a diverse appeal for anesthesiologists, cardiac surgeons and cardiologists desiring comprehensive up-to-date echocardiographic information at their fingertips. Features Updated to include 4 new chapters Now contains more than 600 full-color, high quality clinical images and illustrations Includes the most recent guidelines Retains a compact format that highlights key information Synopsis of cardiac pathology commonly encountered in cardiac surgery patients On-the-spot reference for echocardiographers with a wide range from novice to expert experience.